The Postbiotic Activity of Lactobacillus paracasei 28.4 Against Candida auris - Rossoni, Rodnei Dennis [UNESP]; de Barros, Patrícia Pimentel [UNESP]; Mendonça, Iatã do Carmo [UNESP]; Medina, Rebeca Previate [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Fuchs, Beth Burgwyn; Junqueira, Juliana Campos [UNESP]; Mylonakis, Eleftherios (Frontiers, 2020)
Candida auris has emerged as a medically important pathogen with considerable resistance to antifungal agents. The ability to produce biofilms is an important pathogenicity feature of this species that aids escape of host immune responses and antimicrobial agents. The objective of this study was to verify antifungal action using in vitro and in vivo models of the Lactobacillus paracasei 28.4 probiotic cells and postbiotic activity of crude extract (LPCE) and fraction 1 (LPF1), derived from L. paracasei 28.4 supernatant. Both live cells and cells free supernatant of L. paracasei 28.4 inhibited C. auris suggesting probiotic and postbiotic effects. The minimum inhibitory concentration (MIC) for LPCE was 15 mg/mL and ranges from 3.75 to 7.5 mg/mL for LPF1. Killing kinetics determined that after 24 h treatment with LPCE or LPF1 there was a complete reduction of viable C. auris cells compared to fluconazole, which decreased the initial inoculum by 1-logCFU during the same time period. LPCE and LPF1 significantly reduced the biomass (p = 0.0001) and the metabolic activity (p = 0.0001) of C. auris biofilm. There was also a total reduction (~108 CFU/mL) in viability of persister C. auris cells after treatment with postbiotic elements (p < 0.0001). In an in vivo study, injection of LPCE and LPF1 into G. mellonella larvae infected with C. auris prolonged survival of these insects compared to a control group (p < 0.05) and elicited immune responses by increasing the number of circulating hemocytes and gene expression of antimicrobial peptide galiomicin. We concluded that the L. paracasei 28.4 cells and postbiotic elements (LPCE and LPF1) have antifungal activity against planktonic cells, biofilms, and persister cells of C. auris. Postbiotic supplementation derived from L. paracasei 28.4 protected G. mellonella infected with C. auris and enhanced its immune status indicating a dual function in modulating a host immune response.
Keywords: biofilms; Candida auris; Lactobacillus; postbiotic; probiotic